The Unique Cost of Human Eye Gaze in Cognitive Control: Being Human-Specific and Body-Related? - Li, Kexin; Lu, Aitao; Deng, Ruchen; Yi, Hui (Psichologija, 2022)
This study investigated the eye gaze cost in cognitive control and whether it is human-specific and body-related. In Experiment 1, we explored whether there was a cost of human eye gaze in cognitive control and extended it by focusing on the role of emotion in the cost. Stroop effect was found to be larger in eye-gaze condition than vertical grating condition, and to be comparable across positive, negative, and neutral trials. In Experiment 2, we explored whether the eye gaze cost in cognitive control was limited to human eyes. No larger Stroop effect was found in feline eye-gaze condition, neither the modulating role of emotion. In Experiment 3, we explored whether the mouth could elicit a cost in Stroop effect. Stroop effect was not significantly larger in mouth condition compared to vertical grating condition, nor across positive, negative, and neutral conditions. The results suggest that: (1) There is a robust cost of eye gaze in cognitive control; (2) Such eye-gaze cost was specific to human eyes but not to animal eyes; (3) Only human eyes could have such eye-gaze costs but not human mouth. This study supported the notion that presentation of social cues, such as human eyes, could influence attentional processing, and provided preliminary evidence that the human eye plays an important role in cognitive processing.